Pengaruh Due Professional Care dan Hal Audit Utama terhadap Kualitas Audit: Peran Moderasi Pengalaman Kerja - Amaraneysa, Aisha; Amin, Muhammad Nuryatno (Owner : Riset dan Jurnal Akuntansi, 2024)
The World Bank 2019 survey expressed their concerns about the inconsistent application of audit standards in Indonesia. In response, the Financial Services Authority (OJK) approved the SA 701 Audit Standard to enhance transparency and audit quality. Due Professional Care, Key Audit Matters, and work experience were identified as factors influencing audit quality. The study aims to investigate factor that impact and improve auditors' practices and its understanding. The study was conducted using a quantitative method. The data used in this study were primary data obtained from questionnaires distributed to public accounting firms in DKI Jakarta. Purposive sampling with predetermined criteria was used as the sampling technique and a total of 120 auditors working in 10 audit offices of DKI Jakarta were obtained. The analysis method was multiple regression analysis, processed and tested with IBM SPSS 25. The results of the research indicate that the variables of Due Professional Care and Key Audit Matters have a significant positive influence on Audit Quality. Additionally, Work Experience significantly strengthens the relationship between Due Professional Care and Key Audit Matters with Audit Quality.